Assessment of the Public Administration System of the Republic of Kazakhstan in the Context of a Pandemic - А. N. Zhanbyrbayeva; Ya. A. Yeraliyeva (Экономика: стратегия и практика)
The global pandemic has significantly disrupted the functioning of certain branches of public administration. Still, it has become a springboard for the accelerated development of new technologies, including remote work, a flexible approach to strategic decision-making and services. The purpose of the study is to analyze the public administration system in the context of the pandemic as a whole, the adopted reforms, comprehensive differentiation using specific social methods, comparative methods, and providing recommendations. Individual event analysis of the reforms implemented by our country during the pandemic was also carried out, and the results were analyzed on the basis of this analysis method. The article also analyzes the actions of giant states such as the People’s Republic of China, Great Britain, France, the Netherlands, Turkey, Korea, and Germany during the pandemic to combat the crisis. Summing up the results of the research goal, we came to the conclusion that, first of all, it is necessary to ensure the satisfaction of the population with the country’s public administration system, regulate the healthcare sector, develop medical production, organize full coverage of the people with domestic food products, increase the quantity and quality of export-oriented goods, increase the demand for scientific laboratories and qualified specialists, strengthen information security. The results of the research in the article, i.e. recommendations, can be used in the process of public administration to prevent such gaps in the conditions of rapid action in a crisis.